EXAMINATION OF THE PREDICTION OF FLEXIBILITY FOR LEARNER SATISFACTION IN ONLINE COURSES - AKCAY, Arif (Turkish Online Journal of Distance Education, 2023)
Universities consider student satisfaction in order to improve the online education they give to students and to question the fulfillment of their responsibilities. Student satisfaction may depend not only on the educational institution but also on individual characteristics. One of these individual characteristics is flexibility, which requires multidimensional pedagogical responsibility in online learning environments. The aim of this study is to examine whether the flexibility of time management, the flexibility of teacher contact, and the flexibility of content predict online course satisfaction. In this research, the predictive relational research method was used. 1794 students participated in the research. During an academic term, students took an online Turkish II course at a university’s Distance Education Research and Application Center. According to the results of the analysis, the students’ three flexibility predicts their satisfaction and the model that explains their satisfaction is significant (R2=.60; p<.01). In the model, the variable that most explains student satisfaction is the flexibility of content. In addition, other variables explaining student satisfaction are students’ flexibility in teacher contact and their flexibility in time management. Based on the results of the research, implications, and suggestions are presented.
Keywords: Hayat Boyu Öğrenme; Online Course Satisfaction; Lifelong learning; The Flexibility of Time Management; The Flexibility of Content; The Flexibility of Teacher Contact; Online course satisfaction; the flexibility of time management; the flexibility of teacher contact; the flexibility of content; 4. Education